Casual Talk 100 years Cooperatives Movement with KSU KUSKOP - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 7 December 2022 - Universiti Malaysia Pahang (UMP) received a visit from the Secretary-General (KSU), Ministry of Entrepreneur Development and Cooperatives (KUSKOP), Dato’ Suriani Dato’ Ahmad in conjunction with the 100-Year Cooperatives Movement Casual Chat programme held at UMP Pekan.